2021
DOI: 10.3390/ma14154168
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Defects in 3D-Printed Dielectric Structures via Thermographic Inspection and Deep Neural Networks

Abstract: In this paper, we propose a new method based on active infrared thermography (IRT) applied to assess the state of 3D-printed structures. The technique utilized here—active IRT—assumes the use of an external energy source to heat the tested material and to create a temperature difference between undamaged and defective areas, and this temperature difference is possible to observe with a thermal imaging camera. In the case of materials with a low value of thermal conductivity, such as the acrylonitrile butadiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The modeling strategy is effective for modern complex materials (such as composite materials). The use of DCNNs has been proven to be able to identify the defect parameters of 3D printing materials [130], and the use of RNN models can also predict the plastic deformation of materials with unique geometric shapes (such as 3D materials) [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling strategy is effective for modern complex materials (such as composite materials). The use of DCNNs has been proven to be able to identify the defect parameters of 3D printing materials [130], and the use of RNN models can also predict the plastic deformation of materials with unique geometric shapes (such as 3D materials) [52].…”
Section: Discussionmentioning
confidence: 99%
“…The use of hybrid models can also solve the optimization design of multilayer coatings in perovskite solar cells [129] and evaluate the status of 3D printing structures [130]. A more complex hybrid model is used to predict the properties of the grain boundary (GB).…”
Section: Hybrid Models With Other Algorithmsmentioning
confidence: 99%
“…Due to their properties, CNN networks find many applications in computer vision and image recognition [ 41 ]. Applications in object recognition and tracking [ 41 ], medicine—for imaging diagnosis of diseases [ 52 ] or in technology—for the assessment of the state of structures [ 42 , 45 , 53 , 54 , 55 , 56 ] or design [ 57 ], and testing the properties [ 53 ] of materials, comprise a special area. For example, in [ 52 ], the effectiveness of detecting carious lesions was on average between 82% and 89%.…”
Section: Deep Cnn-based Go Steel Identification Proceduresmentioning
confidence: 99%
“…The CNN are also used in the field of non-destructive testing (NDT). In [ 54 ] and [ 55 ], the CNNs have been used for the automatic defect identification, respectively, in steel elements based on magnetic imaging and in 3D printouts by thermal examination, achieving an overall accuracy of over 90%. The CNN are also used to detect changes in dynamic systems and classify their states based on STFT spectral characteristics [ 58 , 59 , 60 ].…”
Section: Deep Cnn-based Go Steel Identification Proceduresmentioning
confidence: 99%
“…Extracting such a collection from the same data set, which is then assessed by a trained network, is the most often employed approach. In our previous work, we have shown that, for this purpose, the convolutional neural networks may be used [ 40 ], and other researchers have worked on a similar problem [ 41 ]. This results in the obvious issue of a network adjusting to a single−use case, rendering it very inflexible and unsuited for jobs requiring some automation.…”
Section: Introductionmentioning
confidence: 99%